Pembelajaran Toilet Training dalam Melatih Kemandirian Anak - Muhammad Khoiruzzadi; Nur Fajriyah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
Toilet training is one way that teachers can do in the development of children's independence. This study aims to describe the implementation of toilet training in exercising independence in children aged 2-3 years. This research is a field research with descriptive qualitative approach. The source of the data was taken from the results of the class teacher and school principal interviews as well as the observations of the students playing the Al-Ikhlas class aged 2-3 years at the Ulul Albab Integrated Islamic Palace Kraton Pekalongan City. The results of the study show the purpose of toilet training is to train children's independence in toileting, to introduce early on unclean objects, to identify items in the toilet and to properly teach urinating and defecating. The implementation of toilet training starts with planning, that is preparing story material from story books on the themes of activities in the toilet, the implementation is carried out by the teacher using the habituation method and the method of storytelling, and evaluating that the teacher assigns tasks to the child in the form of direct practice about activities related with toilet training